Daily Consumption of Lemon and Ginger Herbal Infusion Caused Tumor Regression and Activation of the Immune System in a Mouse Model of Breast Cancer - AL-ataby, Israa A.; Talib, Wamidh H. (Frontiers in Nutrition, 2022)
The Mediterranean diet includes consumption of various fruits and vegetables. Lemon and ginger are highly popular in the Mediterranean cuisine. The current study aims to evaluate both anticancer and immunomodulatory activities of lemon and ginger combination. The antiproliferative activities of the combination were tested against different cancer cell lines using MTT assay. The degree of apoptosis induction and VEGF expression were detected using ELISA. Balb/C mice were inoculated with the EMT6/P breast cancer cells and received combination water extract orally for 14 days. The effect of the water extract on splenocytes proliferation was measured using the mitogen proliferation assay. Macrophage function was evaluated using the nitro blue tetrazolium assay and pinocytosis was assessed using the neutral red method. GC-MS/MS was used to determine the composition of the combination. The lemon and ginger combination showed significant apoptosis induction and angiogenesis suppression effects. Fifty percent of the mice taking this combination did not develop tumors with percentage of tumor reduction of 32.8%. This combination showed a potent effect in stimulating pinocytosis. Alpha-pinene and α-terpineol were detected in high percentages in the combination water extract. The lemon and ginger combination represents promising options to develop anticancer infusions for augmenting conventional anticancer therapies. Further testing is required to understand the exact molecular mechanisms of this combination.